The Effectiveness of STEM-Based Learning in Teaching 21 st Century Skills in Generation Z Student in Science Learning: A Meta-Analysis - Ichsan Ichsan; Yayat Suharyat; Tomi Apra Santosa; Erwinsyah Satria (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effectiveness of STEM-based learning to train Z generation students' 21st century skills in science learning. This research is a kind of meta-analysis research. The research sample came from an analysis of 16 reputable national and international journals. Data search was obtained through the Google Scholar database, Springer, Hindawi and Eric. Data screening was carried out strictly and thoroughly. The sampling technique is a purposive sampling technique. The data used as the research sample has a relationship with the independent variable and the dependent variable, namely the effectiveness of STEM-based learning on the 21st century skills of Generation Z students in learning science. Data analysis is a qualitative and quantitative data analysis technique by calculating the value of the effect size (ES), the average value and the N-Gain assisted by the JSAP application with the sig value criteria. 0.05. The results showed that the application of STEM-based learning was effective in training the 21st century skills of Genera Z students in science learning with an effect size (ES) value of 1.47 and an N-gain of 0.86 in the high category